Making a Difference in Teacher Education Through Self-Study
XXXII, 260 p.
Keywords: The challenges teacher educators are now facing are of a different nature from those of the past few decades. They have taken on an urgency and a magnitude not witnessed before. Strict government control of education is increasing, the social problems in the schools are more severe, the budget restrictions we face in the university are greater, and the public disillusionment with education, in general, is more than just a passing malaise. This period will be crucial to the future of teacher education; we need to rally together to examine our practice, renew our programs accordingly, collaborate with others, and offer examples of programs that do make a difference. Making a difference in teacher education through self-study: Studies of personal, professional, and program renewal describes the systematic efforts of committed and creative teacher educators to improve their teacher education programs. It describes the accomplishments of individuals (and in part the programs in which they work) who have overcome many of the hurdles teacher educators typically face. These individuals have made a difference in the lives of their students, their colleagues, and many classroom teachers. The book presents research on 15 different teacher education programs and describes individual renewal efforts. The stories -- including both the successes and challenges -- are inspiring and informative. In this age of accountability these teacher educators have used a range of research methods to gather data on their work and in turn used it to guide future decisions. The text includes examples of both large scale research and individual efforts. The common thread among the authors is a commitment to "walking the talk.".